(untitled) (Scientific journal of the Fergana State University, 2024)
A very large amount of water resources accumulate in lakes, and they serve as a natural reservoir. However, since ancient times, lakes have been used not only as reservoirs, but also for the development of fishing and seafood farming. The lakes also charmed people with their unique nature; recreation areas were built around them. Sometimes some lakes cause catastrophic floods, causing great damage to people and their property. They are called dam lakes. Scientific sources contain many records of floods that occurred on dam lakes. In this regard, limnologists conducted many studies and the results obtained were assessed as the most valuable information for that time. For this purpose, the study of limnological studies of different periods and assessment on this basis of the current state of the problem is of great scientific and practical importance. Obtaining a positive solution to this issue is to ensure the water needs of agriculture, prevent floods caused by dammed lakes, reduce the degree of their damage, and most importantly, it allows the determination of scientifically based measures to ensure the safety of the population. Taking into account the above, this article highlights the issues of dammed lakes located in Uzbekistan and adjacent mountainous areas, their research and the aggravation of problems associated with them. To clarify the issue, the results and conclusions of studies conducted in different periods were used. Also, based on hydrological, meteorological and hydrogeological calculation methods, the elements of the water-sedimentation balance of the dam lake system were assessed; in studies aimed at determining the parameters of a collapsing dam, assessing its stability, and reducing the risk of dam failure, special topographic and geodetic and hydraulic research methods, as well as methods of cartographic, geographic similarity and comparison, and mathematical statistics are widely used.